Is education the panacea for economic deprivation of Muslims? Evidence from wage earners in India, 1987 - 2005 - Sumon Kumar Bhaumik; Manisha Chakrabarty (Institute for the Study of Labor (IZA), 2007)
Few researchers have examined the nature and determinants of earnings differentials among religious groups, and none has been undertaken in the context of conflict-prone multi-religious societies like the one in India. We address this lacuna in the literature by examining the differences in the average (log) earnings of Hindu and Muslim wage earners in India, during the 1987-2005 period. Our results indicate that education differences between Hindu and Muslim wage earners, especially differences in the proportion of wage earners with tertiary education, are largely responsible for the differences in the average (log) earnings of the two religious groups across the years. By contrast, differences in the returns to education do not explain the aforementioned difference in average (log) earnings. In conclusion, we discuss some policy implications.
Keywords: J31; 330; Earnings gap; education; decomposition; religion; Einkommensverteilung; Soziale Schicht; Religion; Bildung; Dekompositionsverfahren; Indien